2015
DOI: 10.1111/zph.12222
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Spatial Distribution of Salmonella Infections in the Pennsylvania Raccoon (Procyon lotor)

Abstract: A study was conducted to determine the prevalence and spatial distribution of Salmonella infection in Pennsylvania raccoons (Procyon lotor), common wildlife mammals known to occupy overlapping habitats with humans and domestic food animals. The Pennsylvania Game Commission provided a total of 371 raccoon intestinal samples from trapped and road-killed raccoons collected between May and November 2011. Salmonella was isolated from the faeces of 56 (15.1%) of 371 raccoons in 35 (54%) of 65 counties across Pennsyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
2
13
2
Order By: Relevance
“…Antimicrobial resistance in raccoon Salmonella isolates from our study yielded prevalences similar to other studies (Jardine et al, ; Lee et al, ; Very et al, ). However, only Lee et al, previously reported resistance to nalidixic acid without resistance to ciprofloxacin in Salmonella from raccoons.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Antimicrobial resistance in raccoon Salmonella isolates from our study yielded prevalences similar to other studies (Jardine et al, ; Lee et al, ; Very et al, ). However, only Lee et al, previously reported resistance to nalidixic acid without resistance to ciprofloxacin in Salmonella from raccoons.…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports from varying temperate zone urban, rural and natural environments have provided contradictory results as to the prevalence of Salmonella serovars in raccoons (Compton et al, ; Jardine et al, ; Lee et al, ; Rainwater et al, ; Very et al, ). In tropical urban settings, we found S. Hartford to have the highest prevalence followed by S. Typhimurium and S. Bovismorbificans.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A CRISPR‐based subtyping scheme, CRISPR‐multi‐virulence locus sequence typing (MVLST), is highly discriminatory between unrelated isolates and this has been demonstrated in multiple serovars (Almeida, Medeiros, Rodrigues, Allard, & Falcão, ; DiMarzio, Shariat, Kariyawasam, Barrangou, & Dudley, ; Liu, Barrangou, et al, ; Liu, Kariyawasam, et al, ; Shariat, DiMarzio, et al, ; Shariat, Kirchner, et al, ; Shariat, Sandt, DiMarzio, Barrangou, & Dudley, 2013; Very et al, ; Vosik, Tewari, Dettinger, & M'ikanatha, & Shariat, ). In a previous study from our group, CRISPR‐MVLST was used to analyse human clinical samples of Salmonella Kentucky from Pennsylvania.…”
Section: Introductionmentioning
confidence: 99%